Determinants of Middle and High School Teachers’ Well-Being: A Systematic Review - Issom FL; Agustiani H; Purba FD; Lubis FY (Psychology Research and Behavior Management)
Fitri Lestari Issom,1 Hendriati Agustiani,2 Fredrick Dermawan Purba,2 Fitriani Yustikasari Lubis2 1Psychology Study Program, Faculty of Psychology, Universitas Padjadjaran, Bandung, Indonesia; 2Department of Psychology, Faculty of Psychology, Universitas Padjadjaran, Bandung, IndonesiaCorrespondence: Fitri Lestari Issom, Psychology Study Program, Faculty of Psychology, Universitas Padjadjaran, Bandung, Indonesia, Email fitri22006@mail.unpad.ac.idPurpose: In this review, the determinant of teachers’ well-being in middle and high school teachers and to identify potential avenues for future investigation was evaluated.Patients and Methods: The systematic review of this study was conducted using the Preferred Reporting Items for System Reviews and Meta-Analysis (PRISMA) methodology. We looked through a range of scholarly research on teachers’ well-being that had been published in English and included in Scopus, EBSCO host, Science Direct, and Springer Link. There were 465 publications found throughout the literature search. The final analysis contained 12 publications after duplicates were eliminated and titles, abstracts, and full texts were screened. Articles unrelated to the topic and did not concentrate on TWB in middle and high school were excluded. The findings were checked and verified. A risk-of-bias assessment tool designed for systematic reviews of mixed research (ie, reviews that combine qualitative, quantitative, and/or mixed methods studies) was the Mixed Methods Appraisal Tool (MMAT).Results: There were fourth determinants of middle and high school TWB. The most powerful determinants were physical health, mental and emotional health, social support, professional development and autonomy. Meanwhile, the areas that required further investigation included TWB intervention programs, influential cultural and social factors, research methodology, and measurement procedures.Conclusion: Key determinants of teacher well-being (TWB) in middle and high school, such as physical and mental health, social support, professional development and autonomy, suggest several clinical applications. Targeted mental health resources, wellness initiatives, and strong support networks could significantly enhance TWB. Additionally, empowering teachers through skill development and autonomy may improve their job satisfaction and reduce burnout. Future intervention should consider cultural and social nuances to maximize TWB support.Keywords: determinants factors, teacher well-being, middle and high school teacher, systematic review